FRI0065 Proteomic Profiling Following Immunoaffinity Capture of High-Density Lipoprotein (HDL) Identifies Changes in Multiple HDL-Associated Proteins Following Treatment with Abatacept or Adalimumab in the Ample Study of Patients with Rheumatoid Arthritis. (9th June 2015) - Charles-Schoeman, C.; Gugiu, G.B.; Ge, H.; Shahbazian, A.; Lee, Y.Y.; Wang, X.; Furst, D.E.; Ranganath, V.K.; Maldonado, M.; Reddy, S.T.
Abstract : Objectives: To evaluate changes in high-density lipoprotein (HDL) function and HDL-associated proteins and their association with RA disease activity measures in a subset of patients with active RA initiating therapy with abatacept or adalimumab in the Abatacept Versus Adalimumab Comparison in Biologic-Naïve RA Subjects with Background Methotrexate (AMPLE) study. 1 Methods: Ultra high-pressure liquid chromatography (UHPLC) coupled with ion mobility mass spectrometry (LC-IM-MS) was used to analyse proteins associated with immunoaffinity-captured HDL from plasma of 30 patients with RA randomized to either abatacept (n=15) or adalimumab (n=15) therapy. Proteins were reduced, alkylated and digested with trypsin, and the resulting peptides were identified and quantitated by a Waters NanoAcquity UHPLC system coupled to a Synapt G2 HDMS mass spectrometer fitted with an Ionkey nanoelectrospray source. Standard cholesterol profiles, HDL anti-oxidant function and paraoxonase 1 (PON1) activity were measured by previously published assays. 2 Repeated-measures analyses were performed using mixed-effect linear models with autoregressive covariate structure to model the within-subject covariance over time using available time points from AMPLE. Results: In mixed-effect models controlling for age, sex and treatment group, improvement in inflammation measured by decrease in CRP was associated with increase in total cholesterol levels (p=0.01) irrespective of treatment. Improvement in inflammation (CRP) was also associated with improvement in HDL anti-oxidant function (i.e. decrease in HDL Inflammatory Index [HII]; p=0.01), which was not different between treatment groups. Decreases in CRP were significantly associated with decreases in several HDL-associated proteins including lipopolysaccharide-binding protein, serum amyloid A-I (SAA-I) and inter-alpha-trypsin inhibitor heavy chain H4 (all 3 p values <0.05). Strong trends for decreases in other HDL-associated proteins including fibrinogen (gamma chain) and galectin 3 binding protein associated with decreases in CRP were also noted (both p values=0.10). Adalimumab was associated with a greater increase in PON1 activity (p=0.01) and a trend for greater decrease in HDL-associated SAA-I compared with abatacept (p=0.06). Conclusions: This pilot study showed that decreases in inflammation associated with treatment of active RA, using either abatacept or adalimumab in the AMPLE study, were associated with significant alterations in the HDL proteome, including proteins involved in the immune response, and overall improvement in HDL anti-oxidant function. As the function of HDL has previously been directly linked to CV disease, further characterization of the biomarkers reported here may identify novel molecular connections that contribute to the higher risk of CV disease in patients with active RA, which are improved with effective therapy. References: Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Charles-Schoeman C, et al. Arthritis Rheum 2013;65:2765–72 Disclosure of Interest: C. Charles-Schoeman Grant/research support from: Bristol-Myers Squibb, G. B. Gugiu: None declared, H. Ge: None declared, A. Shahbazian: None declared, Y. Y. Lee: None declared, X. Wang: None declared, D. E. Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, BMS, Cytori, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Speakers bureau: AbbVie, Actelion, UCB (all CME only), V. K. Ranganath Grant/research support from: BMS, Genentech, M. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. T. Reddy: None declared